The Relationship Between Personal Hygiene And The Incidence Of Pediculosis Capitis Among Students Of Sungai Beringin 02 Public Elementary School, District 50 Kota - Letvi Mona; Madhuri Dixit; Nadia Purnama Dewi (Biomedical Journal of Indonesia, 2024)
Introduction. Pediculosis capitis or commonly known as head lice is a skin infection that attacks the human head. It is caused by the ectoparasite Pediculus Humanus Capitis, which lives by sucking blood on the scalp of infected people. One of the factors that can be related to pediculosis capitis is personal hygiene. The general objective of this research is to determine the relationship between personal hygiene and the incidence of pediculosis capitis in students at Sungai Beringin 02 Public Elementary School, Kabupaten 50 Kota. Methods. This research uses an analytical observational method with a cross-sectional approach, namely a study conducted to study the dynamics of the correlation between two variables. The accessible population in this research is all students of Sungai Beringin 02 Public Elementary School, Kabupaten 50 Kota in 2023. Results. This study shows 63.6% of students are not infested with pediculosis capitis. The highest class infested with pediculosis capitis is class 3-4, there are 50%, 95% of students who are infested with pediculosis capitis are female, and 65.5% of students have good personal hygiene. The results of the research show that there is a relationship between personal hygiene and the incidence of pediculosis capitis in students because  68.4% of students who are infested with pediculosis capitis do not have good personal hygiene. Conclusion. The results of bivariate analysis show that there is a significant relationship between the level of personal hygiene and the incidence of Pediculosis Capitis in students at Sungai Beringin 02 Public Elementary School with a p-value of 0.001.